2013
DOI: 10.1136/heartjnl-2013-304746
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Klotho is associated with the presence and severity of coronary artery disease

Abstract: Patients with significant CAD present lower soluble concentrations of Klotho, as well as reduced levels of Klotho gene expression in the vascular wall. Reduced serum Klotho concentrations and decreased vascular Klotho gene expression were associated with the presence and severity of CAD independently of established cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
115
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 47 publications
6
115
3
4
Order By: Relevance
“…Recently, some studies have reported that Klotho deficiency might contribute to the development of atherosclerosis and atherothrombosis. [50][51][52] In our study, we showed that exogenous Klotho administration not only significantly attenuated IS-induced thrombosis, but also retarded the acceleration of atherosclerosis in apoE 2/2 mice with CKD. There are multiple targets of Klotho.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, some studies have reported that Klotho deficiency might contribute to the development of atherosclerosis and atherothrombosis. [50][51][52] In our study, we showed that exogenous Klotho administration not only significantly attenuated IS-induced thrombosis, but also retarded the acceleration of atherosclerosis in apoE 2/2 mice with CKD. There are multiple targets of Klotho.…”
Section: Discussionsupporting
confidence: 52%
“…Indeed, α‐Klotho deficiency in mice leads to a limited vasodilatory response and increased permeability in the endothelial cells among other vascular complications also observed in CKD patients 22, 23, 24, 41. As reported previously in other uremic in vivo models20, 21 and CKD patients,42, 43 we confirmed that impaired kidney function induced downregulation of mRNA and α‐Klotho protein levels in kidney tissue accompanied by lower serum concentrations.…”
Section: Discussionsupporting
confidence: 89%
“…α‐Klotho is an antiaging protein, and its deficiency is associated with a cardiovascular phenotype including arteriosclerosis, vascular calcification, and, importantly, endothelial cell dysfunction 22, 23. In humans, deficiency in serum α‐Klotho correlates with cardiovascular complications 24. However, a direct role of serum α‐Klotho deficiency on endothelial dysfunction in patients with CKD has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…First, the study sample was relatively small. Second, it has been reported that FGF23 level may be higher among subjects with incident myocardial infarction 39) and patients with significant CAD present lower soluble concentrations of Klotho 40) . The current study population underwent chest MDCT under the clinical diagnosis or suspicion of coronary artery disease; therefore, our findings may not be applicable to the general population.…”
Section: Logistic Regression Analysis For the Association Between -Klmentioning
confidence: 99%